2015
DOI: 10.1016/j.ijcard.2015.03.440
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of catheter-based renal denervation on cardiac sympathetic drive and cardiac baroreflex function in heart failure

Abstract: In an ovine model of heart failure, catheter-based RDN did not reduce resting CSNA in the short-term. There was, however, a lack of a reflex increase in CSNA in response to the fall in arterial pressure due to a leftward shift in the baroreflex control of CSNA, which may be due to denervation of renal efferent and/or afferent nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
0
25
1
Order By: Relevance
“…Although producing a modest fall in arterial pressure in 29 obese patients with metabolic syndrome treated with a maximum of one antihypertensive drug, renal nerve ablation failed to decrease MSNA at a 6 mo follow-up (84). In an ovine model of heart failure, catheter-based renal denervation did not reduce elevated levels of cardiac sympathetic nerve activity when measured 24 h after renal denervation (7).…”
Section: Other Potential Determinants Of the Antihypertensive Responsmentioning
confidence: 88%
“…Although producing a modest fall in arterial pressure in 29 obese patients with metabolic syndrome treated with a maximum of one antihypertensive drug, renal nerve ablation failed to decrease MSNA at a 6 mo follow-up (84). In an ovine model of heart failure, catheter-based renal denervation did not reduce elevated levels of cardiac sympathetic nerve activity when measured 24 h after renal denervation (7).…”
Section: Other Potential Determinants Of the Antihypertensive Responsmentioning
confidence: 88%
“…A recent study employed catheter-based renal denervation after the development of CHF in sheep (Booth et al, 2015b ). Despite convincing evidence of complete functional afferent and efferent renal denervation as well as a drop in blood pressure, renal denervation did not decrease cardiac sympathetic tone or improve cardiac baroreflex gain in CHF sheep.…”
Section: Afferent Renal Sympathetic Nerve Activity In Chfmentioning
confidence: 99%
“…After denervation, renal norepinephrine spillover was reduced by an average of 47%, but this response was highly variable between subjects. Much better results have been achieved in both sheep and pigs (Booth et al, 2015b ), but the fact that the renal nerves do not form a network around the main renal artery in man may render such complete denervation impossible (Oldham, 1950 ). The partial efficacy of catheter-based techniques in patients contrasts from surgical denervation, which consistently and completely eliminates renal norepinephrine in all species.…”
Section: Catheter-based Renal Denervationmentioning
confidence: 99%
“…In addition, a recent study investigating the effects of surgical RDN in rats with cardiac dysfunction secondary to chronic pressure overload showed that RDN reduced myocardial fibrosis, increased cardiac β-adrenergic receptor expression and decreased cardiac AT-1 receptor levels (Li et al, 2015 ). In pacing-induced ovine HF, the high resting level of CSNA was not reduced shortly after catheter-based RDN, but the baroreflex-mediated increase in CSNA in response to the fall in BP was inhibited following the procedure (Booth et al, 2015c ). This lack of a reflex increase in CSNA resulted from a leftward shift of the CSNA arterial baroreflex curve (Booth et al, 2015c ).…”
Section: Ablation Of the Renal Nerve Fibers In Heart Failure: Evidencmentioning
confidence: 99%
“…In pacing-induced ovine HF, the high resting level of CSNA was not reduced shortly after catheter-based RDN, but the baroreflex-mediated increase in CSNA in response to the fall in BP was inhibited following the procedure (Booth et al, 2015c ). This lack of a reflex increase in CSNA resulted from a leftward shift of the CSNA arterial baroreflex curve (Booth et al, 2015c ). These findings indicate that RDN can have beneficial cardiac effects in experimental HF, but further studies are required to determine the mechanisms involved.…”
Section: Ablation Of the Renal Nerve Fibers In Heart Failure: Evidencmentioning
confidence: 99%